2020
DOI: 10.1101/2020.06.08.139451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VirusDIP: Virus Data Integration Platform

Abstract: Motivation:The Coronavirus Disease 2019 (COVID-19) pandemic poses a huge threat to human public health. Viral sequence data plays an important role in the scientific prevention and control of epidemics. A comprehensive virus database will be vital useful for virus data retrieval and deep analysis. To promote sharing of virus data, several virus databases and related analyzing tools have been created. Results: To facilitate virus research and promote the global sharing of virus data, we present here VirusDIP, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The Virus Data Integration Platform (VirusDIP [ 50 ], https://db.cngb.org/virus/ncov ) is a system developed at CNGBdb to help researchers find, retrieve and analyze viruses quickly. It declares itself as a general resource for all kinds of viruses; however, to date includes only coronaviruses sequences.…”
Section: Sars-cov2 Search Systemsmentioning
confidence: 99%
“…The Virus Data Integration Platform (VirusDIP [ 50 ], https://db.cngb.org/virus/ncov ) is a system developed at CNGBdb to help researchers find, retrieve and analyze viruses quickly. It declares itself as a general resource for all kinds of viruses; however, to date includes only coronaviruses sequences.…”
Section: Sars-cov2 Search Systemsmentioning
confidence: 99%
“…Although the origin sources provide well-organized data portals (NCBI Virus ( 10 ), the COVID-19 Data Portal https://www.covid19dataportal.org/ and GISAID EpiCoV TM data browser), these do not allow for an integrated search over multiple sources, nor they provide fast selection using sequence variants. A number of other integrated interfaces are being developed in alternative research contexts: UCSC SARS-CoV-2 Genome Browser ( 11 ); 2019nCoVR ( 12 ) at the Chinese National Genomics Data Center; VirusDIP ( 13 ) at the China National GeneBank; CovSeq ( 14 ); and CARD ( 15 ). Compared to other resources, ViruSurf has much stronger query and search capabilities; we use the power of conceptual modeling to structure metadata and to organize data integration and curation; we support search queries allowing to combine filters on metadata, nucleotide and amino acid mutations in an effective and scalable way, treating all of them as first-class citizens.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the predominant approach to combat C. pomonella has been through the use of conventional insecticides (Hu et al, 2020). However, the efficacy of chemical insecticides in controlling this pest is limited due to factors like overlapping generations and the larvae's habit of tunneling into fruit (Huang et al, 2024;Ju et al, 2021). Furthermore, the widespread application of insecticides has led to the development of resistance in C. pomonella (Ju et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that male pupae irradiated with X-rays at a dose of 366 Gy resulted in complete sterility in C. pomonella, albeit with a low mating competitiveness index of 0.01 . The observed side effects of X-ray irradiation, such as reduced mating competitiveness, are likely attributed to its negative impact on flight ability (Huang et al, 2024).…”
Section: Introductionmentioning
confidence: 99%